Muslims of the heartland: how Syrian immigrants made a home in the American Midwest - Curtis, Edward E., IV, 1970- (New York, USA: New York University Press, 2022)
"This book rejects the stereotype of the Midwest as bleached-out Christian country. It unearths a surprising and intimate history of the first two generations of Syrian Muslims in the Midwest who, in spite of discrimination, created a life that was Arab, American, and Muslim all at the same time"--
Muslim South Dakota from Kadoka to Sioux Falls -- Homesteading Western North Dakota -- Peddling in Cedar Rapids, Iowa, a Town of Ethnic Tradition -- Michigan City, Indiana, and Syrian Muslim Industrial Workers -- Muslim Life and the Agricultural Depression in North Dakota -- Cedar Rapids' Grocery Business and the Growth of a Muslim Midwestern Town -- From Sioux Falls and Michigan City to Detroit, Capital of the Muslim Midwest -- Conclusion: A Big Party in the 1950s.
Includes bibliographical references and index.
Keywords: Syrian Americans -- Middle West -- History -- 20th century; Muslims -- Middle West -- History -- 20th century; Muslim families -- Middle West -- Social conditions; Middle West -- Race relations -- History -- 20th century